2010
DOI: 10.1002/ptr.3194
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C pathway is involved in the inhibition by crocetin of vascular smooth muscle cells proliferation

Abstract: Crocetin is a natural carotenoid compound isolated from Gardenia jasminoids Ellis. Our previous study showed that crocetin inhibits angiotensin II (Ang II)-induced proliferation of vascular smooth muscle cells (VSMCs). The present study investigated the involvement of the protein kinase C (PKC) pathway in the growth-inhibitory action of crocetin in VSMCs. The findings showed that PKC activity in the membrane fraction of VSMCs increased following stimulation with Ang II, which was suppressed significantly by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In these group GTPase HRas, Ras-related protein Rab-5A, Ras-related protein Rap-2a and RAF proto-oncogene serine/threonine-protein kinase targets are related to Ras and Raf signaling pathways. In vivo studies have demonstrated that Crocetin has played a therapeutic role in Ras and Raf signaling induced carcinoma in mice (Zhou et al, 2010). Thus our results very well correlate with the experimental evidence.…”
Section: Potential Protein Targets For Crocetinsupporting
confidence: 88%
“…In these group GTPase HRas, Ras-related protein Rab-5A, Ras-related protein Rap-2a and RAF proto-oncogene serine/threonine-protein kinase targets are related to Ras and Raf signaling pathways. In vivo studies have demonstrated that Crocetin has played a therapeutic role in Ras and Raf signaling induced carcinoma in mice (Zhou et al, 2010). Thus our results very well correlate with the experimental evidence.…”
Section: Potential Protein Targets For Crocetinsupporting
confidence: 88%
“…The total proteins (50 or 100 μg) were resolved on 10% SDS-PAGE gel and transferred to nitrocellulose membranes, as previous described. (Zhou, Xiang, He, & Qian, 2010a, 2010b. The membranes were blocked in Tris Buffered Saline with Tween containing 3% bovine serum albumin for 1 hr at room temperature and further incubated with special antibodies, including FXR1, TGR5, and β-actin (1:1,000) at 4°C overnight.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…PKC-α, a conventional PKC isoform, has been shown to mediate VSMCs proliferation in rat, human and bovine [9,16,17]. Thus, we focused on the role of PKC-α in the suppression of TSETT on angiotensin II-induced VSMCs proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Our result exhibited that the mRNA expressions of c-fos and c-jun were increased clearly by angiotensin II and the increases were inhibited significantly by pretreatment with TSETT This result implied that the proto-oncogene mediated the suppressive effect by TSETT on the proliferation in VSMCs. In fact, previous study showed that chelerythrine chloride, a specific inhibitor of PKC, did not affect activation of ERK1/2 [9], which means that angiotensin II -induced ERK1/2 activation might be independent of PKC in VSMCs. These data suggest that the inhibition of proto-oncogene expression by TSETT attribute to the inhibitory effect on both PKC and ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation